2015
DOI: 10.1007/s13402-015-0247-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-101-2, miR-125b-2 and miR-451a act as potential tumor suppressors in gastric cancer through regulation of the PI3K/AKT/mTOR pathway

Abstract: Background Gastric cancer (GC) is a deadly malignancy worldwide. In the past, it has been shown that cellular signaling pathway alterations play a crucial role in the development of GC. In particular, deregulation of the PI3K/AKT/mTOR pathway seems to affect multiple GC functions including growth, proliferation, metabolism, motility and angiogenesis. Targeting alterations in this pathway by microRNAs (miRNAs) represents a potential therapeutic strategy, especially in inhibitor-resistant tumors. The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 55 publications
(63 reference statements)
4
84
0
Order By: Relevance
“…For example, high levels of the miRNA Let-7c induce cell cycle arrest by targeting CDC25a [99]. Similarly, the tumour suppressor activities of Hsa21-encoded miR-99a [100] and miR-125b-2 [101] could contribute to lung hypoplasia. The biology of the lung in Down syndrome can also be affected by overexpression of Hsa21 genes in nonresident cells.…”
Section: Genetic Influence Of Trisomy 21 On Pulmonary Diseasementioning
confidence: 99%
“…For example, high levels of the miRNA Let-7c induce cell cycle arrest by targeting CDC25a [99]. Similarly, the tumour suppressor activities of Hsa21-encoded miR-99a [100] and miR-125b-2 [101] could contribute to lung hypoplasia. The biology of the lung in Down syndrome can also be affected by overexpression of Hsa21 genes in nonresident cells.…”
Section: Genetic Influence Of Trisomy 21 On Pulmonary Diseasementioning
confidence: 99%
“…Moreover, miRNAs have been reported to stimulate the PI3K-AKT-mTOR pathway in various diseases [2123]. Therefore, we sought to determine whether PI3K-AKT-mTOR signalling is regulated by the ST8SIA family and miRNAs in FTC.…”
Section: Introductionmentioning
confidence: 99%
“…Oncogenic miRNAs block the function of certain mRNAs, of tumor suppressors whereas tumor suppressive miRNAs produce an anti-tumor effect [10, 11]. Several studies have reported that miRNAs can regulate several aspects of human gastric cancer pathogenesis, including metastasis, invasion, and self-renewal by targeting the EGR2 [12], MAPK [13] and PI3K/AKT signaling pathways [14]. Therefore, targeting specific miRNAs could be a possible alternative for the treatment of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%